Teaching and quality of teaching: Conceptions of higher education professors in Sao Tome and Principe - Grácio, Luísa; Aguiar, Helga; Pires, Heldemerina; Carapeto, Maria João (Frontiers in Education, 2023)
Higher education is a fundamental resource to achieve the 2030’ Sustainable Development Goals (SDG) defined by the United Nations. Specifically, SDG4 advocates the access to quality education for all, including tertiary education. Besides, higher education is expected to be an important condition for achieving other SDGs. Developing countries face particularly important challenges to accomplish these higher education goals. Thus, it is crucial to understand how to promote quality in higher education in the specific context of each country. Among the most important factors influencing higher education quality are professors’ conceptions of teaching. These conceptions influence teaching action and have a direct impact on students' own academic performance and learning outcomes. Teaching conceptions seems to be strongly influenced by cultural values and social norms and in African countries there is little research in this field. This study aims to characterize and understand both the conceptions of teaching and on facilitating factors and barriers to university teaching held by the University of Sao Tome and Principe (USTP) faculty. The data were obtained through semi-structured interviews to 19 university professors and analyzed through qualitative and quantitative methodologies. The results suggest the prevalence of teacher-centered / transmission-oriented and student-centered / learning-oriented conceptions of university teaching. In addition, other conceptions highlight professors’ competences and the relationship between teaching and context variables. Organizational aspects of the education system, material resources and facilities, characteristics and training of the faculty, teaching action, and students’ characteristics, are mentioned both as facilitators and barriers to university teaching. Some contributions emerged from the professors’ conceptions that could inspire improvements at the USTP teaching, therefore contributing to facing changes and challenges of a society in development